2020
DOI: 10.1177/0886260520983273
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Correlates of Violence Among American Indian and Alaska Native Youth: A Brief Report

Abstract: The purpose of this paper is to document the scope and correlates of past 6-month victimization among American Indian (AI) and Alaska Native (AN) youth. Types of victimization under investigation included sexual assault, dating violence, bullying, sharing of nude photos, sexual harassment, homophobic teasing, and racism. Participants were 400 AI and AN youth in grades 7–10 who completed a survey in school. Results documented concerning rates of all forms of victimization among AI and AN youth during the past 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Several case accounts implicate feelings of not mattering in suicide attempts and deaths due to suicide (e.g., Addington & Mancuso, 2009;Nolle et al, 2012) and going beyond these cases and anecdotal reports, there is some initial research that links low mattering with suicidality (Elliott et al, 2005;Joiner et al, 2009;Milner et al, 2016), including suicidal behaviors (Holden et al, 2018). New research links mattering at school with less suicide ideation among American Indian and Alaskan native youth (Edwards et al, 2020).…”
Section: Mattering In the Real Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…Several case accounts implicate feelings of not mattering in suicide attempts and deaths due to suicide (e.g., Addington & Mancuso, 2009;Nolle et al, 2012) and going beyond these cases and anecdotal reports, there is some initial research that links low mattering with suicidality (Elliott et al, 2005;Joiner et al, 2009;Milner et al, 2016), including suicidal behaviors (Holden et al, 2018). New research links mattering at school with less suicide ideation among American Indian and Alaskan native youth (Edwards et al, 2020).…”
Section: Mattering In the Real Worldmentioning
confidence: 99%
“…A new investigation based on survey data from almost 25,000 high school youth from New Hampshire links physical and sexual violence in dating situations with feelings of not mattering in one's community (Edwards & Neal, 2017). Other research with youth also links feelings of not mattering with a reported history of interpersonal victimization (see Hamby et al, 2020) while acknowledging the role of mattering at school in reducing the likelihood of being a victim (Edwards et al, 2020).…”
Section: Mattering At the Relationship Levelmentioning
confidence: 99%
“…The girls in the city (comparison) sample were on average 13.7 years old (range = 12 to 18; SD = 1.29), in grades 6 to 12 (median = 8th, SD = 1.07), and the majority identified as heterosexual (80.1%). The girls in the city sample come from a larger multiple baseline study examining the impact of a youth-led initiative on reducing rates of sexual assault (Edwards et al, 2021); all data collected in the city sample that is presented in this article occurred before the implementation of the initiative.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in a nationally representative sample of urban American Indian high school students, researchers documented that 16.4% of American Indian youth reported being physically forced to have sex during the past year (compared to 6.6% of White youth; Rutman et al, 2008). Research suggests that sexual assault is related to a host of deleterious outcomes in American Indian youth, including (but not limited to) depression, suicidal ideation, and binge drinking (Edwards et al, 2021). Thus, the prevention of sexual assault among American Indian girls is of critical public health importance.…”
Section: Effectiveness Of a Sexual Assault Self-defense Program For A...mentioning
confidence: 99%
“…What might we be missing in how we are framing SRV prevention that may not be currently resonating with them? This may be especially important in communities with a large presence of Native youth for which we know very little about effective SRV prevention (Edwards et al, in press; Edwards et al, under review). PAR methods are those that involve participants as decision‐makers who collaborate with researchers on all parts of a project.…”
Section: Introductionmentioning
confidence: 99%